2000
DOI: 10.1038/35010000
|View full text |Cite
|
Sign up to set email alerts
|

CpG methylation is maintained in human cancer cells lacking DNMT1

Abstract: Hypermethylation is associated with the silencing of tumour susceptibility genes in several forms of cancer; however, the mechanisms responsible for this aberrant methylation are poorly understood. The prototypic DNA methyltransferase, DNMT1, has been widely assumed to be responsible for most of the methylation of the human genome, including the abnormal methylation found in cancers. To test this hypothesis, we disrupted the DNMT1 gene through homologous recombination in human colorectal carcinoma cells. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
287
2
11

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(316 citation statements)
references
References 24 publications
16
287
2
11
Order By: Relevance
“…26 For instance, the expression of p16 in the CRC cell line HCT116 is diminished by a mutation on one allele and epigenetic inactivation by promoter hypermethylation of the other allele. 27 In addition, we have shown that PTEN expression in sporadic CRC is influenced by mutations or allelic loss of one allele and promoter hypermethylation of the other allele. 28 Promoter hypermethylation might occur at a very early state.…”
Section: Discussionmentioning
confidence: 95%
“…26 For instance, the expression of p16 in the CRC cell line HCT116 is diminished by a mutation on one allele and epigenetic inactivation by promoter hypermethylation of the other allele. 27 In addition, we have shown that PTEN expression in sporadic CRC is influenced by mutations or allelic loss of one allele and promoter hypermethylation of the other allele. 28 Promoter hypermethylation might occur at a very early state.…”
Section: Discussionmentioning
confidence: 95%
“…For this task, we utilized a genetic DNMT knockout HCT116 model system (Rhee et al, 2000(Rhee et al, , 2002. We initially confirmed the genotype and phenotype of the DNMT knockout lines by measuring DNMT1 and DNMT3b expression by Western blot and reverse transcriptase-polymerase chain reaction (RT-PCR), respectively (Supplemental Figure 2a and b), and by analysing global genomic DNA methylation levels using Liquid chromatography-mass spectrometry (LC-MS) (Song et al, 2005) (Supplemental Figure 2c).…”
Section: Activation Of Cg-x Gene Expression By Genetic Knockout Of Dnmentioning
confidence: 99%
“…Recent studies using tumor suppressor genes have provided information concerning the role that specific DNMTs play in mediating gene repression and promoter methylation in human cancer cells (Rhee et al, 2000(Rhee et al, , 2002Leu et al, 2003;Robert et al, 2003;Ting et al, 2004). Some of these studies suggest a critical independent role for DNMT1 (Robert et al, 2003), whereas others implicate cooperativity between DNMT1 and DNMT3b in mediating tumor suppressor gene repression (Rhee et al, 2000(Rhee et al, , 2002Ting et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A human colon cancer cell line, HCT116 deficient in DNMT1 following targeted recombination, demonstrates demethylation of pericentromeric satellite sequences (Rhee et al, 2000), whereas HCT116 cells lacking both DNMT1 and DNMT3B contain demethylated satellite 2 and Alu repetitive sequences (Rhee et al, 2002) and demonstrate increased chromosomal instability (Karpf and Matsui, 2005). Additional studies of the doubly targeted cells suggest that at least some histone modifications occur before alterations in DNA methylation (Bachman et al, 2003).…”
Section: Introductionmentioning
confidence: 99%